BACKGROUND KNOWLEDGE IN EFL READING COMPREHENSION: LECTURERS' PERSPECTIVE & CLASSROOM STRATEGIES - abdullah miftachul irvan (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
Abstract: This article aims to find out three main sectors related to background knowledge in reading comprehension. The lecturers' perspective about the role of background knowledge, the instructional strategies they employ to activate students' background knowledge, and the difficulties they encounter when activating students' background knowledge. The research design of this study was descriptive qualitative study. Eleven reading lecturers from five different universities in Indonesia participated in this study. Two instruments were used: an online Google Form questionnaire adapted from Al-Jahwari and Al-Humaidi (2015), and an online semi-structured interview. The researcher analyzed the summary, conclusion based on the online data from the online Google Form questionnaire and online interview session. The results of this research indicated an intense agreement about the role of background knowledge in text comprehension, a serious reliance on some techniques and a clear connection about the difficulties of resources such as students’ low linguistic competence and lack of lecturers training on background knowledge theory and its instructional techniques.Keywords: background knowledge, classroom strategies, and reading comprehension.